2020
DOI: 10.1002/cam4.3106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the immune profile of oral tongue squamous cell carcinomas with advancing disease

Abstract: We investigated whether a unique immune response was instigated with the development of oral tongue squamous cell carcinomas (OTSCC), with/without nodal involvement, with/without recurrent metastatic disease, or within tumor involved nodes. One hundred and ten formalin‐fixed paraffin‐embedded samples were collected from a retrospective cohort of 67 OTSCC patients and 10 non‐cancerous tongue samples. Targets including CD4, CD8, FOXP3, PD‐L1, and PD‐1 were analyzed by immunohistochemistry. The Nanostring PanCanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
4
18
1
Order By: Relevance
“…This is why, in the study presented here, we focused on IHC-based analysis to better understand the landscape of immune cells in HNSCC. In other IHC-based studies of HNSCC, the focus was on a more general description of the relation of the immune cell types rather than their spatial distribution (25,33) or on a single location such as that of oral tongue cancers (34). The study of Meehan et al included a mixture of PT and recurrent disease (RD) HNSCC of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…This is why, in the study presented here, we focused on IHC-based analysis to better understand the landscape of immune cells in HNSCC. In other IHC-based studies of HNSCC, the focus was on a more general description of the relation of the immune cell types rather than their spatial distribution (25,33) or on a single location such as that of oral tongue cancers (34). The study of Meehan et al included a mixture of PT and recurrent disease (RD) HNSCC of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we have shown that there are a large number of deregulated EV proteins in plasma from patients with and without nodal OTSCC compared with non-cancer controls. We highlight that this is in stark comparison with our tissue-based gene expression study which showed negligible changes in primary tissues of OTSCC with and without nodal disease and non-cancer controls [ 52 ]. Although our earlier study utilized tissues and targeted immuno-cancer genes and the current study utilized plasma and was untargeted, we expected some overlap.…”
Section: Discussionmentioning
confidence: 56%
“…In other works concerning OSCC, PD-L1 expression on TCs was observed with variable frequency ranging from approximately 10 to 90% of cases [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The studies differed in the size of the study group, selection of patients, antibody clones used, and the way of assessing PD-L1 expression; the two latter factors in particular significantly influence the final results of the study.…”
Section: Discussionmentioning
confidence: 97%